Prevalence of Oral Normal Variance in Healthy Elderly Patients: A Descriptive Study on Oral Pseudo-Lesions - Mahdani, Fatma Yasmin; Parmadiati, Adiastuti Endah; Ernawati, Diah Savitri; Suryanijaya, Vint Erawati; Inastu, Candrika Ramya; Radithia, Desiana; Ayuningtyas, Nurina Febriyanti; Surboyo, Meircurius Dwi Condro; Pratiwi, Aulya Setyo; Marsetyo, Riyan Iman (International Archives of Otorhinolaryngology, 2022)
Introduction The aging process in the elderly can change the condition of the oral cavity, regarding both clinical appearance and function. The oral mucosa becomes more susceptible to mechanical damage and irritant agents. Any changes in the oral mucosa, including normal variance, should be examined. This is especially true for the elderly, to improve oral health and prevent any abnormalities.Objective To describe the prevalence of oral normal variance in healthy elderly patients.Methods An observational descriptive study with a cross-sectional design with total sampling conducted from March to April 2020.Results Among the 117 elderly patients who participated in this study, 58 were described as healthy without any comorbidities. From those subjects, there were 117 cases of normal variance in the oral mucosa. The three most prevalent issues were fissured tongue (93.1%), coated tongue (58.62%), and crenated tongue (27.59%).Conclusion Fissured tongue is a normal variance of the oral mucosa that is commonly found in healthy elderly patients.
Keywords: elderly; fissured tongue; human & health; oral mucosa; pseudo lesion